Family Formations in Contemporary South Africa: Does South African Marriage Law Protect Lived Realities?. (6th December 2020) - Osman, Fatima
Abstract: In the 21st century, families are constituted differently to the typical Western Judeo-Christian nuclear family comprising of a mother, father, and children. While some individuals may marry, others may choose not to do so or, at the other end of the spectrum, marry several individuals. This article critically examines whether South African marriage law adequately protects contemporary family formations. The examination reveals that unfortunately – but perhaps not unsurprisingly – the heteronormative nuclear family continues to be positioned as the baseline for the conferral of rights with opposite-sex civil marriages often receiving the greatest protection in South African law. Despite the legislative recognition of civil unions and customary marriages, the realisation of rights by individuals in these fringe groups is hindered by the creation of a complex legislative framework and practical difficulties encountered in the implementation of the law. Furthermore, notwithstanding years of legislative deliberation on the matter, unmarried partners and those in religious marriages enjoy only ad hoc protection through case law and piecemeal legislative provisions. While judicial activism in this arena may be lauded, the limited nature of judgments has led to continuous litigation for the realisation of rights. Statutory reform is thus required to ensure the equal treatment of all marriages, reconcile and simplify existing statutory law, address practical difficulties in the implementation of the law, and govern social reality.